A model for star formation in cosmological simulations of galaxy formation - Lozano, F. (2021)
We present a new model to describe the star formation process in galaxies, which includes the description of the different gas phases - molecular, atomic, and ionized - together with its metal content. The model, which will be coupled to cosmological simulations of galaxy formation, will be used to investigate the relation between the star formation rate (SFR) and the formation of molecular hydrogen. The model follows the time evolution of the molecular, atomic and ionized phases in a gas cloud and estimates the amount of stellar mass formed, by solving a set of five coupled differential equations. As expected, we find a positive, strong correlation between the molecular fraction and the initial gas density, which manifests in a positive correlation between the initial gas density and the SFR of the cloud.